The Influence of Procrastination and Low Time Management on Student Self Efficacy (at MA Soebono Mantofani) - Kharisma Danang Yuangga; Denok Sunarsi (Universitas Negeri Makassar, 2018)
Procrastination is the behavior that can not take advantage of time or procrastinate doing something. The purpose of this study was to determine the effect of procrastinating habits and low time management on student self efficacy in MA Soebono Mantofani. The method used is descriptive method with an associative approach. The sampling technique used was proportional random sampling using a sample of 61 respondents. The analysis tool uses validity test, reliability test, classic assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are the delaying habits have a negative effect on student self-efficacy of 41.0%. Hypothesis testing is obtained tcount <ttable or (-6,406 <2,001), so that H0 is accepted and H1 is rejected, meaning that there is no positive and significant influence between procrastination on student self-efficacy in MA Soebono Mantofani. The low time management has a negative effect on student self-efficacy by 39.9%. Hypothesis testing is obtained tcount <ttable or (-6.262 <2.001) so that H0 is accepted and H2 is rejected, meaning that there is no positive and significant influence between low management time on student slf Efficacy on. Simultaneous test of procrastinating habit and low time management affect the student self efficacy with a contribution of 41.7%, while the remaining 58.3% is influenced by other factors. Hypothesis testing obtained the value of Fcount> Ftable or (20.767> 2.760), thus Ho is rejected and H3 is accepted. This means that there is a simultaneous influence between procrastinating habits and low time management on student self efficacy in MA Soebono Mantofani.